TO THE QUESTION OF INCREASING THE ACCURACY OF ECHOLOCATION MEANS OF MEASURING THE LEVEL OF MEDIUM SEPARATION IN RESERVOIRS - Ashanin, V. N.; Mel'nikov, A. A.; Isaev, S. G.; Tsurikov, S. A. (Известия высших учебных заведений. Поволжский регион:Технические науки, 2020)
Background. In commercial accounting, the task of accurately measuring the level of liquid and bulk materials stored and transported in tanks is very relevant. The aim of this work is to analyze ways to reduce the influence of the parameters of the ultrasound propagation medium on the measurement accuracy of echolocation level gauges and develop recommendations for improving the proposed method and device for level measurement. Materials and methods. Experimental and theoretical studies of the method and microprocessor-based device previously proposed by the authors for measuring the level of separation of media in tanks showed the presence of a methodological error determined by the radial propagation of an ultrasonic wave in a gaseous medium when reflected from the boundaries of separation of media and elements of the tank structure. Analysis of the propagation path of reflected and re-reflected ultrasonic waves in a tank of a given design showed the presence of a methodological error, which can be eliminated by introducing a digital correction in the measurement result. Results. The well-known methods of increasing the accuracy of ultrasonic level meters are considered. A microprocessor-based implementation of the level meter is proposed, which differs in the independence of the propagation velocity of an ultrasonic wave from the parameters of the gas medium of the reservoir, which provides high metrological characteristics with a relatively simple hardware implementation. This allows the developed level gauge to be used in the custody transfer of various liquid and bulk materials in tanks. Conclusions. The introduction of a digital correction into the measurement result, taking into account the design parameters of the tank and the radial propagation of an ultrasonic wave when reflected from the surfaces of the controlled substance and the elements of the tank structure, provides high metrological and operational characteristics of the developed microprocessor level gauge.